Ketamine treatment for individuals with treatment-resistant depression: longitudinal qualitative interview study of patient experiences - Karen Lascelles; Lisa Marzano; Fiona Brand; Hayley Trueman; Rupert McShane; Keith Hawton (BJPsych Open, 2021)
Background Ketamine has recently received considerable attention regarding its antidepressant and anti-suicidal effects. Trials have generally focused on short-term effects of single intravenous infusions. Research on patient experiences is lacking.